2014
DOI: 10.1177/0013916514533189
|View full text |Cite
|
Sign up to set email alerts
|

Floor Plan Connectivity Influences Wayfinding Performance in Virtual Environments

Abstract: The structure of the physical environment can have a significant influence on individuals' ability to orient within it. We asked participants to perform a cued wayfinding task in two virtual environments to test the hypothesis that spatial orientation skills are indeed affected by the physical complexity of the environment. The two virtual environments used for testing differed solely in one objective measure of plan complexity, that is, the average number of connections at each decision point or terminal corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 57 publications
1
51
1
Order By: Relevance
“…When investigating environment intelligibility and legibility, the ease of visual representation should not be mistaken with simplicity. Complex environment can be as comfortable as a space with minimal visual design if aspect such as geometry, rhythm and connectivity is present (Slone et al [5]). The theory has been supported by wayfinding studies such as Mahdzar and Safari's [6] findings that strongly associated geometry with legibility due to it facilitates mental mapping process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When investigating environment intelligibility and legibility, the ease of visual representation should not be mistaken with simplicity. Complex environment can be as comfortable as a space with minimal visual design if aspect such as geometry, rhythm and connectivity is present (Slone et al [5]). The theory has been supported by wayfinding studies such as Mahdzar and Safari's [6] findings that strongly associated geometry with legibility due to it facilitates mental mapping process.…”
Section: Resultsmentioning
confidence: 99%
“…But Slone et al [5] could not rule out the effect of landmark visual features on participant cognitive mapping. Instead, they suggested that their saliency could be a variable factor in future wayfinding experiments to measure their effect.…”
Section: Environmental Legibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have shown the ability to navigate in an unfamiliar environment is affected by the complexity of the layout (Slone et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%